2014
DOI: 10.1002/pon.3565
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers' awareness of illness and attitude toward disclosure during chemotherapy for advanced cancer

Abstract: A large portion of family caregivers may not know the patients' exact status. This study also suggests that the family caregivers' attitudes may differ from patients' and may be associated with patients' QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
(55 reference statements)
2
19
0
Order By: Relevance
“…The caregivers' preference determines the extent of patients' awareness of their prognosis, and thus, the lack of patients' involvement in sharing information is at the basis of the Asian family‐centered model. Similar to the findings in Korea , our study demonstrated a significant discrepancy in poor‐prognosis disclosure preference between patients and caregivers, and the extent of discordance increased with patients' worsening disease status. Furthermore, caregivers' poor‐prognosis disclosure preference was not related to cancer patients' QoL or perceived stress.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The caregivers' preference determines the extent of patients' awareness of their prognosis, and thus, the lack of patients' involvement in sharing information is at the basis of the Asian family‐centered model. Similar to the findings in Korea , our study demonstrated a significant discrepancy in poor‐prognosis disclosure preference between patients and caregivers, and the extent of discordance increased with patients' worsening disease status. Furthermore, caregivers' poor‐prognosis disclosure preference was not related to cancer patients' QoL or perceived stress.…”
Section: Discussionsupporting
confidence: 86%
“…The association between poor‐prognosis disclosure preference and QoL of cancer patients has been investigated in different cultures . Consistent with Kim and Chan's results , we found that cancer patients with a positive poor‐prognosis disclosure preference had better QoL, while their matched caregivers had lower stress levels. Moreover, family caregivers with a positive poor‐prognosis disclosure preference also reported increased physical function.…”
Section: The Relationship Between Poor‐prognosis Disclosure Preferencsupporting
confidence: 89%
“…In many areas of the world, family members have been reported to be an obstacle to CDD to patients by asking medical professionals not to tell the truth . In our former study, family members preferred to hide cancer diagnoses from patients to protect them from perceived emotional harm …”
Section: Resultsmentioning
confidence: 79%
“…To assess the awareness of the prognosis and perception of the goals of therapy, we adapted and modified the following two self-report items, just as was done in previous studies with patients with advanced cancer [14,15]. To assess perceptions of the goals of therapy, we asked the patients the following question: BWhat is the purpose of your treatment?^Patients were categorized into the Baccurate awareness^group if they used terms including Breduce my pain/symptom management or extend my lifetime,^but if they used Bto recover from my cancer/illness^or BI do not know,^the patients were classified into the Binaccurate awareness^category.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the study by Andruccioli et al [14] evaluated the awareness of patients regarding their prognosis, and the findings of this study showed that 62 % of cancer patients were not aware of the progression of their disease. More recently, a study that was conducted in South Korea reported that approximately 90 % of the incurable cancer patients had an unrealistic expectation about their disease progression during chemotherapy [15]. Just as with patients' expectation of disease course, a limited number of studies have investigated perceptions of treatment intent in cancer patients with varying results.…”
Section: Introductionmentioning
confidence: 94%